2015
DOI: 10.7235/hort.2015.14188
|View full text |Cite
|
Sign up to set email alerts
|

Chitooligosaccharide Prolongs Vase Life of Cut Roses by Decreasing Reactive Oxygen Species

Abstract: Chitooligosaccharide (COS), as antioxidant, extensively applied to food and juice preservation. In the present study, influences of COS on vase life and ornamental value of cut roses were investigated. Results showed that vase life of cut roses treated by COS was longer 6.4 days than one of control and ornamental character of cut roses was improved effectively by COS. The increase of vase life and ornamental value were chiefly governed by that COS improved water absorption capacity of cut roses. Besides that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(45 reference statements)
2
5
0
Order By: Relevance
“…Chitooligosaccharide also decreased the contents of superoxide anion and hydrogen peroxide during senescence of cut roses (Jing and Li, 2015). Our observations show that philodendron plu jeeb leaves exposed to eucalyptus essential oil had lower H 2 O 2 levels than untreated control leaves (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Chitooligosaccharide also decreased the contents of superoxide anion and hydrogen peroxide during senescence of cut roses (Jing and Li, 2015). Our observations show that philodendron plu jeeb leaves exposed to eucalyptus essential oil had lower H 2 O 2 levels than untreated control leaves (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…ex Klatt) led to taller plants, with more leaves, shoots, flowers, and corms [ 90 ]. The vase life of cut rose flowers ( Rosa hybrida L.) “Red France” was also prolonged by CHT [ 91 ]. The largest number of studies on the effects of CHT deal with fruit crops.…”
Section: Application Of Cht On Crop/food Plantsmentioning
confidence: 99%
“…Numerous literatures had shown the effect of chitosan on the postharvest quality of flowers. It has also been applied to raise the vase life of cut flower like Heliconia bihai L. [19] and roses [20]. Ali et al [21] demonstrated that applying 1-MCP or CTS-NPs after harvest is a very viable approach for preserving damask rose postharvest quality during storage.…”
Section: Introductionmentioning
confidence: 99%